Ethical Leadership as a Prerequisite for Sustainable Development, Sustainable Finance, and ESG Reporting - Krambia-Kapardis, Maria; Stylianou, Ioanna; Savva, Christos S. (My University, 2023)
The first part of the chapter will contextualize sustainable development and disentangle it from environmental, social, and governance (ESG). The second part will locate the leadership qualities needed which synthesizes sustainable development and ESG reporting, while the third part will put it in context of sustainable finance. As advocated by BlackRock (Sustainability goes mainstream. 2020 Global Sustainable Investing Survey. https://www.blackrock.com/corporate/literature/publication/blackrock-sustainability-survey.pdf, 2020), sustainability is here to stay, and over time investors have demonstrated their interest in addressing ESG considerations. ESG includes human rights; environmental pollution; healthcare; social problems; elimination of poverty; equal rights in the workplace; stronger compliance with local, state, federal, and international laws; diversity; etc. The European Commission (sustainable finance and EU taxonomy: commission takes further steps to channel money towards sustainable activities https://ec.europa.eu/commission/presscorner/detail/en/ip_21_1804, 2021a; What is sustainable finance. A new sustainable finance strategy and implementation of the action plan on financing sustainable growth. https://ec.europa.eu/info/business-economy-euro/banking-and-finance/sustainable-finance/overview-sustainable-finance_en, 2021b) added transparency to ESG, especially in cases of risks regarding the financial and worldwide economy. Is it possible to have a sustainable business and sustainable finance without ethical leadership? In support of Sharma et al. (Leadersh Org Dev J 40(6):712–734, 2019), many leaders today consider ethics important. It is considered that the leaders ought to look out for the people, fairness, sustainability, and integrity. Leaders need to be open to allocating power, giving clear ethical directions at their workplace, building respect, honesty, sincerity, equality, and transparency. It has also been argued that leaders need to foster trustworthy relationship between people that work in the same workplace, thus creating an ethical corporate culture, in other words, being effective leaders (Duggan, What are the key elements of ethical leadership in an organization? https://yourbusiness.azcentral.com/key-elements-ethical-leadership-organization-8819, 2018). In the final part of the chapter, the findings of a study of 153 companies that are considered ethical and sustainable in 24 countries and 11 different industries will be discussed using an econometric model. The authors conclude that companies that are considered ethical and sustainable need to have ethical leaders who will drive and foster a corporate ethical culture so they can have sustainable finance. As illustrated in this chapter, firms that disclose their ESG policies are sustainable and resilient but a driving force behind that is the ethical leadership that fosters and incorporates compassion, resilience, and the creation of a fair and trustworthy workplace.